Dynamic magnetic characteristics of obliquely sputtered Co2FeSi film with ultrahigh in-plane uniaxial anisotropy. (16th November 2016) - Xu, Zhan; Zhang, Zhi; Hu, Fang; Liu, Er; Xu, Feng
Abstract: We performed systematically studies on the magnetostatic and magnetodynamic properties of obliquely deposited Co2 FeSi thin films. By varying the oblique deposition angle of Co2 FeSi films, we induced a large in-plane uniaxial magnetic anisotropy field with the maximum value of 626.7 Oe at oblique angle of 39°, which significantly enhanced its zero-field ferromagnetic resonance (FMR) frequency up to 10.8 GHz. The magnetodynamic parameters such as Gilbert damping factor and exchange stiffness of Co2 FeSi films were determined from the uniform FMR mode and the first perpendicular standing spin-wave, respectively. It is found that the Gilbert damping factor can be easily tuned from 0.006 to 0.013 by changing oblique deposition angle, whereas the exchange stiffness stays almost constant. These Co2 FeSi films with tunable magnetic properties might be a good candidate for applications in both conventional and spintronics microwave devices.